Raymond Carver : An Oral Biography - Halpert, Sam, 1920- (Book collections on Project MUSE., 1995)
Raymond Carver has become a literary icon for our time. When he died in 1988 at the age of fifty, he was acclaimed as the greatest influence on the American short story since Hemingway. Carver's friends were the stuff of legend as well. In this rich collection - greatly expanded from the earlier When We Talk about Raymond Carver - of interviews with close companions, acquaintances, and family, Sam Halpert has chronologically arranged the reminiscences of Carver's adult life, recalling his difficult "Bad Raymond" days through his second life as a recovering alcoholic